Perancangan Interior Restoran Dengan Penerapan Self Producing and Consuming Hydroponic Vegetables di Malang - Natasha Andrea Putri (Intra, 2017)
The need for food is increasing as the number of urban population in the world increases. One of the food we need is vegetable, one of human staple food. The increasing number of people has caused an increasing demand for the land, which has an impact on the cultivated land in the bigger city. Vegetables in urban city must be brought from out of town because of the inadequate urban farmland, causing the vegetables in urban city not fresh, not to mention if uncertain weather conditions make vegetable supply hampered. Seeing those problems, hydroponics became an answer needed by the urban society. Lettuce Urban Farming Restaurant is presented in Malang city with the concept of